Indoor fungal growth on variable antifungal at different wall finishing on plasterboard - Sunar, N.M.; Subramaniam, Tamil Selvan; Zulkifly, N.F.; Parjo, Umi Kalthsom; Er, Ching Ming; Leman, Abdul Mutalib; Khalid, Amir; Shaari, Muhammad Farid; Abdul Rashid, Azrin Hani; Zaidi, E.; Azhar, A. T. S. (Science Publishing Corporation, 2018)
Various health complaints often been attributed to pollution and the poor quality of the indoor air. If there is good practice in building design, construction, and maintenance, the structures should remain dry. However, when there is moisture damage, the materials may be in contact with water for prolonged times, which inevitably leads to microbial growth or even total deterioration of the building material. Antimicrobial coating is designed to generate a surface that is easy to clean and can also incorporate active agents, commonly called antifungal, that prevent microbial colonization, the subsequent growth and bio-deterioration of the substrate. This paper presents the sustainable treatment for indoor environment quality in buildings by examining the application of potassium sorbate, zinc salicylate, and calcium benzoate that used as food industry preservatives as indoor antimicrobial agents. Four types of wall finishing used on plasterboard substrate: acrylic paint, glycerol based-paint, thin wallpaper, and thick wallpaper. The result indicated that potassium sorbate is the best bio compound to react as antifungal agent to prohibit the growth of indoor fungi. All the antifungal shows difference level of their effectiveness from each other. Only 40% of fungi were able to grow on thin wallpaper by using potassium sorbate as antifungal agent.